2000
DOI: 10.1038/sj.onc.1203860
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the major histocompatibility complex (MHC) class I heavy chain, TAP1 and LMP2 genes by the human papillomavirus (HPV) type 6b, 16 and 18 E7 oncoproteins

Abstract: We have examined the possibility that the E7 proteins of the high-risk human papillomavirus (HPV) type 16 and 18 and the oncogenic adenovirus (Ad) type 12 E1A protein share the ability to down-regulate the expression of components of the antigen processing and presentation pathway, as a common strategy in the evasion of immune surveillance during the induction of cell transformation. Expression of the HPV 18 E7 oncoprotein, like Ad 12 E1A, resulted in repression of the major histocompatibility complex (MHC) cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
1
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 36 publications
5
112
1
8
Order By: Relevance
“…In contrast, in oncogenic HPV infections, the 2 major transforming proteins E6 and E7 would complement the inhibitory effect of the lesser transforming protein E5 on the MHC class I pathway. HPV-16 E7 can repress the MHC class I heavy chain gene promoter, 39 thus likely replacing the inhibitory action of BPV on the same promoter, and in addition can bind directly to TAP, thus further contributing to the downregulation of HLA class I. 21 Furthermore, both HPV E6 and E7 can inhibit the type I IFN pathway, thus preventing the IFN-mediated release of E5-induced blockage in HLA class I trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in oncogenic HPV infections, the 2 major transforming proteins E6 and E7 would complement the inhibitory effect of the lesser transforming protein E5 on the MHC class I pathway. HPV-16 E7 can repress the MHC class I heavy chain gene promoter, 39 thus likely replacing the inhibitory action of BPV on the same promoter, and in addition can bind directly to TAP, thus further contributing to the downregulation of HLA class I. 21 Furthermore, both HPV E6 and E7 can inhibit the type I IFN pathway, thus preventing the IFN-mediated release of E5-induced blockage in HLA class I trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…16,[30][31][32] In the case of TAP1, the abnormality is linked to the reduced activity of the bidirectional LMP2/TAP1 promoter, which is strongly modulated by the E7 oncoproteins of the respective HPV type. 33 The transcriptional suppression of the LMP2/TAP1 promoter can also account for the impaired LMP2 expression, which is often found in these malignant cells. However, no information is available regarding the mechanism(s) underlying the TAP2 downregulation in cervical carcinoma cells.…”
Section: Defects In Tap Expression And/or Functionmentioning
confidence: 99%
“…Many viruses and tumours evade the T-cell-mediated immune response, primarily by reducing the levels of surface MHC class I, thus reducing the presentation of viral/tumour antigens (Garcia-Lora et al, 2003;Hewitt, 2003). We have previously shown that the E7 oncoproteins of the high-risk HPV16 and 18 types are able to repress the activity of promoters encoding components of the MHC class I antigen processing and presentation pathway (Georgopoulos et al, 2000) and recent data further suggest that HPV16 E7 interacts with the MHC class I heavy chain promoter in HPV16-transformed human cells (Li et al, 2006). Here, we have used two complementary approaches to evaluate the effect of HPV16 and 18 E7 expression on the levels of cell-surface MHC class I molecules and consequent effects on natural killer (NK) cell recognition.…”
mentioning
confidence: 99%